2020
DOI: 10.1002/cne.25030
|View full text |Cite
|
Sign up to set email alerts
|

Novel circular RNA 2960 contributes to secondary damage of spinal cord injury by sponging miRNA‐124

Abstract: Recent studies have shown that circular RNAs (circRNAs) are involved in many human diseases, but their roles in secondary damage after spinal cord injury (SCI) remain unclear. In the current study circRNA sequencing was performed in the damaged tissues of SCI rats on the seventh day after injury, and related molecular mechanisms were investigated. Quantitative PCR validations of molecules that exhibited significantly altered expression in SCI mice were performed. Gene ontology and Kyoto Encyclopedia of Genes a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(18 citation statements)
references
References 31 publications
1
17
0
Order By: Relevance
“…There was also a study of 7 days after SCI. Results showed that differentially expressed circRNAs related with "metabolic process, " "intracellular organelles, " "nucleic acid binding, " and "MAPK signaling pathway" (Chen et al, 2020). These results suggest that circRNAs participate in the transcription, metabolism, and other crucial biological processes in cells to regulate the process of repair after SCI.…”
Section: Circrna Expression Profile In Scimentioning
confidence: 83%
See 3 more Smart Citations
“…There was also a study of 7 days after SCI. Results showed that differentially expressed circRNAs related with "metabolic process, " "intracellular organelles, " "nucleic acid binding, " and "MAPK signaling pathway" (Chen et al, 2020). These results suggest that circRNAs participate in the transcription, metabolism, and other crucial biological processes in cells to regulate the process of repair after SCI.…”
Section: Circrna Expression Profile In Scimentioning
confidence: 83%
“…It was proved that circRNA_2960 could aggravate the inflammatory response and induce apoptosis at the site of injury. The study further demonstrated that blocking the expression of circRNA_2960 could be beneficial to the recovery of spinal cord injured tissues (Chen et al, 2020). However, the functional relationship between miRNA-124 and mRNA remains to be explored by subsequent researches.…”
Section: Upregulated Circrnasmentioning
confidence: 91%
See 2 more Smart Citations
“…By GO (Gen Ontology) and KEGG (Kyoto Encyclopedia of Genes and Genomes) analysis, dysregulation of circRNAs expression profiles have been found during the immediate, intermediate, and acute phases of secondary traumatic SCI (Qin et al, 2019 ; Zhou et al, 2019 ; Liu et al, 2020 ; Chen et al, 2021 ; Xu et al, 2021 ). Indeed, the potential function of circRNAs after acute traumatic SCI in rats were predicted by bioinformatic analysis on the three criteria (cellular components, biological process, and molecular functions), revealing the upregulated circRNAs were associated with nuclear proteins while downregulated circRNAs to proteins active in the cytoplasm (Zhou et al, 2019 ) and proposing that circRNAs may participate through different molecular mechanisms in SCI pathology.…”
Section: Circrnas In Scimentioning
confidence: 99%